A computer controlled pendulum with position readout - Hauptfleisch, Helge; Gasenzer, Thomas; Meier, Karlheinz; Nachtmann, Otto; Schemmel, Johannes (American journal of physics, 2010)
We have designed and constructed a physical pendulum that allows us to demonstrate its behavior for a variety of forces and initial conditions. All parameters in the equation of motion can be defined by the user. The apparatus can demonstrate phenomena ranging from simple undamped harmonic oscillations to chaotic behavior. The position of the pendulum and the derived quantities such as the velocity and acceleration can be stored for later analysis.
Gesehen am 11.04.2023